Comparison of Non-Operative Treatment and Appendectomy in Non-Perforate Appendicitis in Children - Ahmad Hassan Khan, Allah Nawaz, Khalid Mahmood, Raza Farrukah, Khawaja Arshad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Comparison of non-operative treatment and appendectomy in non-perforate appendicitis in children. Study Design: Comparative analytical study Place and Duration of Study: Department of Surgery, DHQ Teaching Hospital, Sargodha from 1st January 2022 to 31st March 2023. Methodology: Two hundred children within the age of 5-15 years were enrolled. The children were included on the basis of their clinical presentation of appendicitis which was correlated with their biochemical ultrasound findings. The children included in the non-operative group were tagged as group 1 while those in operative group were labelled as Group 2. Children within non-operative treatment group 1 were administered IV meropenem as a 10 mg per kg dose 8 hourly as well as metronidazole in 20 mg per kg once a day IV divided dosage as 8 hourlies for 48 hours. Children in the operative treatment group 2 were administered 3 antibiotic doses and were operated for through modified laparoscopic procedure, however where required open appendectomy was conducted through modifies McBurney’s incision followed by muscle-splitting. Results: 85% of the participants were recovered without any surgery for appendicitis. Highest success rate was observed in 5-8years of age group. In present study, age and baseline variables of both study groups are almost same. No significant difference in either group was observed in terms of temperature, age, TLC, neutrophils, CRP and weight. Conclusion: Non-operative study group demonstrated high success rate in which 85% of the participants were recovered without any surgical intervention. Keywords: Appendectomy, Conservative, Surgical intervention, Modifications.